2013
DOI: 10.1002/jbm.b.33063
|View full text |Cite
|
Sign up to set email alerts
|

Applications of modern sensors and wireless technology in effective wound management

Abstract: The management of chronic wounds has emerged as a major health care challenge during the 21st century consuming, significant portions of health care budgets. Chronic wounds such as diabetic foot ulcers, leg ulcers, and pressure sores have a significant negative impact on the quality of life of affected individuals. Covering wounds with suitable dressings facilitates the healing process and is common practice in wound management plans. However, standard dressings do not provide insights into the status of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 39 publications
0
57
0
Order By: Relevance
“…There is also significant focus on incorporating drugs, silver nanoparticles, and plant‐derived compounds, including essential oils and honey, which exhibit antimicrobial properties. Finally, the real‐time detection of the wound bed environment, including pH or temperature, as indicators of the status of the wound has been explored . The integration of different types of biosensors within wound dressings has been proposed as the future of smart devices, capable of real time sensing and monitoring the wound.…”
Section: Introductionmentioning
confidence: 99%
“…There is also significant focus on incorporating drugs, silver nanoparticles, and plant‐derived compounds, including essential oils and honey, which exhibit antimicrobial properties. Finally, the real‐time detection of the wound bed environment, including pH or temperature, as indicators of the status of the wound has been explored . The integration of different types of biosensors within wound dressings has been proposed as the future of smart devices, capable of real time sensing and monitoring the wound.…”
Section: Introductionmentioning
confidence: 99%
“…However, NO has a half-life less than 10 seconds making it difficult to measure. Investigators have tried to measure wound fluid NO levels indirectly through wound fluid nitrate, induced NO response and fasting urine [81,84]. Boykin concluded that deprivation of NO activity contributes to impaired healing and a comprehensive method to monitor NO, MMP, and bacterial load could accelerate healing in chronic wounds [77].…”
Section: Biochemical Markersmentioning
confidence: 99%
“…Incorporation of temperature‐sensing devices into dressings to monitor wound temperature is currently being investigated . The temperature in the wound bed can be continuously monitored by placing miniaturized sensors in the dressing.…”
Section: Temperaturementioning
confidence: 99%
“…The temperature in the wound bed can be continuously monitored by placing miniaturized sensors in the dressing. This can be achieved with a radio frequency identification device (RFID) or a platinum‐based sensor, using electrical resistance to calculate temperature . Infrared thermometers have been developed to assess the risk of ulceration by monitoring the temperature gradient of intact skin, correlating the rate of lower‐extremity ulceration with increased temperature of the skin at risk …”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation